THE INFLUENCE OF WORK STRESS ON THE ACHIEVEMENT OF WORK TARGETS WITH MOTIVATION AS AN INTERVENING VARIABLE (Case Study of New York Medical Doctor and Chemical Assitant Laboratory) - Martin Uribe; Bob Feinberg (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
In this study the population is New York Medical Doctor and Chemical Assitant Laboratory, namely 32 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population, totaling 32 people, will be used as a research sample. The results of the first hypothesis research are accepted, meaning that Social Security (X) has a significant effect on Work Motivation (Y1). ). the second hypothesis is accepted, meaning that Social Security (X) has a significant effect on Employee Performance (Y2). the third hypothesis is accepted, meaning that Work Motivation (Y1) is an intervening variable that mediates the effect of Social Security (X) on Employee Performance (Y2).